The concentration of chlorophyll-a and its relationship with the sea surface temperature, through satellite images and in-situ data, in the bays of Sechura and Paita - Ramírez, Gilberto (2020)
The validation of the Sea Surface Temperature (SST) estimated from images of the MODIS and VIIRS sensors has been carried out, for the study area delimited between the longitudes of 83o - 80oW and latitudes of 3o - 7oS respectively, in the period from 2001 to 2016 with data from the SST in-situ. Likewise, the monthly average data of the Concentration of Chlorophyll-a (CCA) and TSM VIIRS for the Sechura Bay, in the period from 2012 to 2018, have been related. The in-situ data of TSM are registered by IMARPE, (2000 - 2015). The daily and monthly CCA and TSM images for the study area are obtained from the Ocean Color portal. SeaDAS version 7.5.3 image processing software has been used on Linux Ubuntu 16.04 with netcdf format. The monthly averages of SST-MODIS and the in-situ SST at the Paita station present a correlation coefficient R = 0.96, so we can propose its use in models of oceanographic variables. According to the provisional climatological average of SST (2008-2015) for the bays of Sechura and Paita, the temperature values range between 19.5 °C and 22 °C, with a standard deviation of 0.26 °C. The frequency histogram of the climatological SST for Sechura Bay shows a bimodal distribution skewed to the right. The Split Window NLSST algorithm for MODIS and VIIRS overestimated the in-situ measurements of SST. Sechura Bay presents a significant positive correlation (R = 70.4%) between SST and CCA. It has been observed that the increase in temperature influences the increase in the CCA of the area.